Empowerment and Well-Being of Persons with Disabilities: Islamic Teachings on Inclusive Livelihood in the Qur'an - Billah, Muktashim; Kemala, Rosmalina; Larhzizer, Fouad; Harakan, Ahmad (The Center for Disability Studies and Services Brawijaya University, 2025)
This study explores the empowerment of persons with disabilities through guidance from Qur'anic verse Surah al-Nūr/24:61, offering ethical and spiritual frameworks to reduce discrimination and enhance well-being. The research emphasizes applying Qur'anic principles, including compassionate care, spiritual psychology, and ability-based empowerment, to the lives of persons with disabilities. Using an analytical exegesis method that incorporates historical, linguistic, and legal contexts, as well as literature reviews, the findings underscore the significance of eliminating stigma through empathy, enhancing mental well-being through spiritual connections, and empowering individuals according to their abilities. The verse directs able-bodied people to engage in inclusive social interactions, fostering acceptance and support for persons with disabilities. The study concludes that integrating Qur'anic values into social policies provides a comprehensive approach to creating inclusive and just societies, while offering insights for developing religiously informed, disability-inclusive policies that address the needs and dignity of all individuals.